Disease Activity Indices for Pouchitis: A Systematic Review. Issue 4 (28th June 2021) - Sedano, Rocio; Nguyen, Tran M; Almradi, Ahmed; Rieder, Florian; Parker, Claire E; Shackelton, Lisa M; D'Haens, Geert; Sandborn, William J; Feagan, Brian G; Ma, Christopher; Jairath, Vipul
Abstract: Background: Several indices exist to measure pouchitis disease activity; however, none are fully validated. As an initial step toward creating a validated instrument, we identified pouchitis disease activity indices, examined their operating properties, and assessed their value as outcome measures in clinical trials. Methods: Electronic databases were searched to identify randomized controlled trials including indices that evaluated clinical, endoscopic, or histologic pouchitis disease activity. A second search identified studies that assessed the operating properties of pouchitis indices. Results: Eighteen randomized controlled trials utilizing 4 composite pouchitis disease activity indices were identified. The Pouchitis Disease Activity Index (PDAI) was most commonly used (12 of 18; 66.7%) to define both trial eligibility (8 of 12; 66.7%), and outcome measures (12 of 12; 100%). In a separate search, 21 studies evaluated the operating properties of 3 pouchitis indices; 90.5% (19 of 21) evaluated validity, of which 42.1% (8 of 19) evaluated the construct validity of the PDAI. Criterion validity (73.7%; 14 of 19) was evaluated through correlation of the PDAI with fecal calprotectin (FCP; r = 0.188 to 0.71), fecal lactoferrin (r = 0.570 to 0.582), and C-reactive protein (CRP; r = 0.584). Two studies assessed correlation of the modified PDAI (mPDAI) with FCP (r = 0.476 and r = 0.565, respectively). Fair to moderate inter-rater reliability of the PDAI (k = 0.440) and mPDAI (k = 0.389) was reported in a single study. Responsiveness of the PDAI pre-antibiotic and postantibiotic treatment was partially evaluated in a single study of 12 patients. Conclusions: Development and validation of a specific pouchitis disease activity index is needed given that existing instruments are not valid, reliable, or responsive.